2020
DOI: 10.1186/s12910-020-00510-5
|View full text |Cite
|
Sign up to set email alerts
|

Usage of do-not-attempt-to-resuscitate orders in a Swedish community hospital – patient involvement, documentation and compliance

Abstract: Background To characterize patients dying in a community hospital with or without attempting cardiopulmonary resuscitation (CPR) and to describe patient involvement in, documentation of, and compliance with decisions on resuscitation (Do-not-attempt-to-resuscitate orders; DNAR). Methods All patients who died in Kalmar County Hospital during January 1, 2016 until December 31, 2016 were included. All information from the patients’ electronic chart was analysed. Results Of 660 patients (mean age 77.7 ± 12.1 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
(23 reference statements)
0
4
1
Order By: Relevance
“…We found that DNAR decisions were discussed with 38% of patients. This contrasts with the study by Bertilsson et al [ 26 ] in which discussions with patients were only conducted in 14% of cases. Varying study populations and methods could partially explain this difference, i.e., there may be a difference between what is documented in the patients’ medical records and the participants’ responses to a questionnaire.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…We found that DNAR decisions were discussed with 38% of patients. This contrasts with the study by Bertilsson et al [ 26 ] in which discussions with patients were only conducted in 14% of cases. Varying study populations and methods could partially explain this difference, i.e., there may be a difference between what is documented in the patients’ medical records and the participants’ responses to a questionnaire.…”
Section: Discussioncontrasting
confidence: 64%
“…It is unclear whether this has led to an overall increase in the number of DNAR orders in Sweden. However, a recent study [ 26 ] suggests that such an increase has taken place as 88.6% of all deaths over a period of one year at a Swedish county hospital had a DNAR order in place.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, physicians consider that they have lack of knowledge when to issue DNAR order and how patients and their relatives should be involved in the decision process [6]. Disagreement on codification and registration has also been reported [7,8]. Electronic patient records (EPR) have improved the quality of documentation and information management in general [9].…”
Section: Introductionmentioning
confidence: 99%
“…7 Only individuals can determine what is beneficial or harmful to them, therefore all medical decisions must rest with the patients. 8 It is the task of ethicists to bolster protection of patient autonomy by limiting instances of unwarranted substitute judgments, while risk managers strive to increase the likelihood that treatment received is concordant with treatment desired. A cornerstone to this effort is the creation of advance directives that stipulate the scope of the treatment patients want in the event they are seriously ill and lack the capacity to express their desires at the time.…”
Section: Trajectory Of Advance Directivesmentioning
confidence: 99%
“…27 Moreover, patients who are older, suffered unwitnessed arrests, or have no shockable rhythm, should be told that they are unlikely to live long enough to be discharged from the hospital even if they survive CPR, and that if they do survive they are likely to undergo repeated resuscitation attempts that only prolong death and may impair their QoL Only patients can decide: "whether or not an instant death in ventricular fibrillation is preferable to a death because of cancer in a couple of weeks." 8 A binary choice obscures the reality of these potential multiple causes and outcomes, 28 increasing the risk of over-or under-treatment by oversimplifying treatment planning.…”
Section: Creating the Ordermentioning
confidence: 99%